Transcriptional Suppression of Connexin43 by TBX18 Undermines Cell-Cell Electrical Coupling in Postnatal Cardiomyocytes - Kapoor, Nidhi (American Society for Biochemistry and Molecular Biology, 2011)
T-box transcription factors figure prominently in embryonic cardiac cell lineage specifications. Mesenchymal precursor cells expressing Tbx18 give rise to the heart's pacemaker, the sinoatrial node (SAN). We sought to identify targets of TBX18 transcriptional regulation in the heart by forced adenoviral overexpression in postnatal cardiomyocytes. Neonatal rat cardiomyocytes (NRCMs) transduced with GFP showed sarcolemmal, punctate Cx43 expression. In contrast, TBX18-transduced NRCMs exhibited sparse Cx43 expression. Both the transcript and protein levels of Cx43 were greatly down-regulated within 2 days of TBX18 transduction. Direct injection of TBX18 in the guinea pig heart in vivo inhibited Cx43 expression. The repressor activity of TBX18 on Cx43 was highly specific; protein levels of Cx45 and Cx40, which comprise the main gap junctions in the SAN and conduction system, were unchanged by TBX18. A reporter-based promoter assay demonstrated that TBX18 directly represses the Cx43 promoter. Phenotypically, TBX18-NRCMs exhibited slowed intercellular calcein dye transfer kinetics (421 ± 54 versus control 127 ± 43 ms). Intracellular Ca(2+) oscillations in control NRCM monolayers were highly synchronized. In contrast, TBX18 overexpression led to asynchronous Ca(2+) oscillations, demonstrating reduced cell-cell coupling. Decreased coupling led to slow electrical propagation; conduction velocity in TBX18 NRCMs slowed by more than 50% relative to control (2.9 ± 0.5 versus 14.3 ± 0.9 cm/s). Taken together, TBX18 specifically and directly represses Cx43 transcript and protein levels. Cx43 suppression leads to significant electrical uncoupling, but the preservation of other gap junction proteins supports slow action potential propagation, recapitulating a key phenotypic hallmark of the SAN.